PENGARUH KOMPENSASI, PENGALAMAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI NEGERI SIPIL (PNS) PADA DINAS PEKERJAAN UMUM DAERAH KABUPATEN MOROWALI - Nismawati, Nismawati (Katalogis, 2016)
The objectives of this study are: 1) to determine and analyze the influence of compensation, work experience, and organizational commitment on civil servants performance in the Department of Public Works Morowali Regency; 2) to determine and analyze the influence of compensation on civil servants performance; 3) to determine and analyze the influence of work experience on civil servants performance; 4) to determine and analyze the influence of organizational commitment on civil servants performance. The type of this research is descriptive causal and it involves 56 respondents who are selected by census method. Based on the tests result, it is found that: 1) compensation, work experience, and organizational commitment simultaneously influence the performance of civil servants in The Department of Public Works positively and significantly; 2) compensation positively and significantly influence civil servants performance; 3) work experience positively and significantly influence civil servants performance; 4) organizational commitment positively and significantly influence civil servants performance.